2022
DOI: 10.3390/nu14051111
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle-Related Risk Factors of Orthorexia Can Differ among the Students of Distinct University Courses

Abstract: Orthorexia nervosa (ON) is defined as the excessive attention on healthy eating, and studies especially focused on food quality ON prevalence in university students can be extremely variable. The objective of this study is to investigate whether there was a difference in ON risk between health-scientific, economic-humanistic, sport sciences and dietetics and nutrition students, and to evaluate if lifestyle-related ON risk factors (dieting, physical activity, drugs and supplements use) could have an impact in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…Furthermore, the results showing that Brazilian students in the areas of health, human, exact, language, and biological studies presented self-reports of orthorexic behaviors corroborate and expand the generality of the results found by Guglielmetti et al [22], who observed a prevalence of orthorexia in 30% of the sample of 671 students from 4 different university courses, finding no statistical differences among the results of each course. On the other hand, they differ from the results obtained by Grajek et al [23], who observed a higher risk of orthorexia in health students (63.5%) compared to students from other areas of knowledge (25.8%).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Furthermore, the results showing that Brazilian students in the areas of health, human, exact, language, and biological studies presented self-reports of orthorexic behaviors corroborate and expand the generality of the results found by Guglielmetti et al [22], who observed a prevalence of orthorexia in 30% of the sample of 671 students from 4 different university courses, finding no statistical differences among the results of each course. On the other hand, they differ from the results obtained by Grajek et al [23], who observed a higher risk of orthorexia in health students (63.5%) compared to students from other areas of knowledge (25.8%).…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, they differ from the results obtained by Grajek et al [23], who observed a higher risk of orthorexia in health students (63.5%) compared to students from other areas of knowledge (25.8%). It is suggested that further studies comparing the prevalence of orthorexia nervosa in students from different areas of knowledge and in the general population are carried out, with the aim of confirming the current results and those found by Guglielmetti et al (2022) [22], which will make it possible to expand the scope of these findings.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations